2022
DOI: 10.1007/s00170-022-10631-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical investigation of micro-textures fabrication by ultrasonic surface rolling process

Abstract: Surface texturing is a potential approach to achieving excellent surface performance. To realize high precision and efficiency in micro-texturing fabrication, a surface texturing method utilizing an ultrasonic surface rolling process is proposed.Firstly, the feasibility and geometric controllability of micro-texture preparation using ultrasonic surface rolling process are analyzed. Then a contact theory model of ultrasonic rolling texturing process is established, which can describe the geometric relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Wu et al [5] investigated the friction properties of GCr15 with varying textures after USRP processing and found that the friction reduction performance under the cross-texture shape was the best. Meng et al [6] simulated and experimented with USRP on 5140 steel and found that USRP can prepare textures on the surface of parts. The parts processed by USRP have significantly improved the residual stress [7], microhardness [8], microstructure [9], mechanical properties [10], and so on.…”
mentioning
confidence: 99%
“…Wu et al [5] investigated the friction properties of GCr15 with varying textures after USRP processing and found that the friction reduction performance under the cross-texture shape was the best. Meng et al [6] simulated and experimented with USRP on 5140 steel and found that USRP can prepare textures on the surface of parts. The parts processed by USRP have significantly improved the residual stress [7], microhardness [8], microstructure [9], mechanical properties [10], and so on.…”
mentioning
confidence: 99%